2021
DOI: 10.1111/jfpp.15379
|View full text |Cite
|
Sign up to set email alerts
|

Essential oils as flavoring and preservative agents: Impact on volatile profile, sensory attributes, and the oxidative stability of flavored extra virgin olive oil

Abstract: Spices and aromatic herbs have been used since ancient times for flavor, aroma, color, and preservation of food and beverages. They are a rich source of bioactive and functional ingredients to which numerous food-related properties are associated. Among the active ingredients, essential oils have received particular attention due to their wide array of biological activities including antioxidant, antimicrobial, anti-inflammatory, anti-nociceptive, anti-carcinogenic, and acaricidal activities, among others (Har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 34 publications
2
11
0
Order By: Relevance
“…In a recent study, Teneva et al [ 20 ], focused on biological preservation of mayonnaise and found interesting results with a combination of the probiotic Lactobacillus plantarum , basil, and dill EOs (22.7% alpha-phellandrene in the latter) significantly decreasing the number of undesired microflora, making this combination an effective biological preservative for mayonnaise. Benkhoud et al [ 104 ] incorporated thyme EO (1.3% alpha-phellandrene) to extra virgin olive oil proving its ability to preserves its nutritional quality, and sensory attributes, and, most of all, to improve its oxidative stability during long-term storage. Tavakkoli et al [ 34 ] evaluated the effects of tomato residuum extract (TRE) dipping and Arabic gum (AG) coating enriched with dill EO (DEO), with alpha-phellandrene as a main component, on the shelf-life extension of refrigerated trout fillets, and found that treatments TRE 3%-AG-DEO 2% and TRE 6%-AG-DEO 2% had significantly effects.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study, Teneva et al [ 20 ], focused on biological preservation of mayonnaise and found interesting results with a combination of the probiotic Lactobacillus plantarum , basil, and dill EOs (22.7% alpha-phellandrene in the latter) significantly decreasing the number of undesired microflora, making this combination an effective biological preservative for mayonnaise. Benkhoud et al [ 104 ] incorporated thyme EO (1.3% alpha-phellandrene) to extra virgin olive oil proving its ability to preserves its nutritional quality, and sensory attributes, and, most of all, to improve its oxidative stability during long-term storage. Tavakkoli et al [ 34 ] evaluated the effects of tomato residuum extract (TRE) dipping and Arabic gum (AG) coating enriched with dill EO (DEO), with alpha-phellandrene as a main component, on the shelf-life extension of refrigerated trout fillets, and found that treatments TRE 3%-AG-DEO 2% and TRE 6%-AG-DEO 2% had significantly effects.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, several landmark studies have shown that enrichment of EVOO/VOO can improve their oxidative stability, nutritional quality, and organoleptic properties (Benkhoud et al., 2021 ; Rubió et al., 2012 ). In this study, it has been demonstrated that the enrichment of EVOO with DAS preserves its quality in term of major (e.g., fatty acids) and minor compounds (e.g., phenolics, pigments, sterols, and vitamin E), probably by inhibiting lipid peroxidation and the formation of free radicals.…”
Section: Discussionmentioning
confidence: 99%
“…The major restriction is related to the careful choice of the quantities of the added EO or mixtures of EOs so that the end product exerts balanced sensorial characteristics. Bay laurel EO is rarely reported as a flavoring agent of olive oil [ 140 ], in contrast to the frequent use of other EOs from the Mediterranean flora [ 137 , 140 , 141 , 142 , 143 , 144 , 145 ]. Its addition in olive oil by 0.05% ( v/w ) was found to be promising as far as it concerns 1,8-cineol stability during the thermal oxidation process and under photo-oxidation conditions.…”
Section: Applications To Olive Industry Productsmentioning
confidence: 99%